Psychological Aspects of Offenders and Penal Sanctions Effectiveness in Child Sexual Explotation Cases : Case Study Number : 1477/Pid.Sus/2024/Pn Plg - Via Geneti Lomban Toruan; Indah Sri Utari (Universitas Negeri Semarang, 2026)
Cases of child sexual exploitation through digital media (CSAM) continue to escalate; however, law enforcement frequently concentrates solely on imposing retributive prison sentences without adequately considering the offender's psychological profile. This study analyzes Court Decision Number 1477/Pid. Sus/PN Plg, in which the defendant was sentenced to 11 years in prison without a mandate for clinical rehabilitation, to evaluate the effectiveness of such sanctions from a forensic psychological perspective and emphasize the urgency of implementing a Double Track System to mitigate recidivism. Employing a qualitative method with a normative juridical and case study approach, the research finds that pure imprisonment is substantively ineffective as it fails to address the cognitive distortions and psychosexual disorders prevalent among offenders, which cannot be remediated through physical isolation alone. Neglecting these psychological dimensions in judicial verdicts compromises long-term public protection once the offender completes their sentence. Consequently, this research affirms that achieving substantive justice requires the Indonesian criminal justice system to transform towards a Double Track System as mandated by the TPKS Law, wherein the integration of forensic psychological assessments in court proceedings becomes an absolute prerequisite for determining appropriate action sanctions (rehabilitation) to effectively break the cycle of child sexual violence.